Pharmacogenetic Testing for Prevention of Severe Cutaneous Adverse Drug Reactions - Chang, Chih-Jung; Chen, Chun-Bing; Hung, Shuen-Iu; Ji, Chao; Chung, Wen-Hung (Frontiers in Pharmacology, 2020)
Severe cutaneous adverse reactions (SCAR), such as Stevens-Johnson syndrome (SJS), toxic epidermal necrolysis (TEN), and drug rash with eosinophilia and systemic symptoms (DRESS), are idiosyncratic and unpredictable drug-hypersensitivity reactions with a high-mortality rate ranging from 10% to over 30%, thus causing a major burden on the healthcare system. Recent pharmacogenomic studies have revealed strong associations between SCAR and the genes encoding human-leukocyte antigens (HLAs) or drug-metabolizing enzymes. Some of pharmacogenetic markers have been successfully applied in clinical practice to protect patients from SCAR, such as HLA-B*15:02 and HLA-A*31:01 for new users of carbamazepine, HLA-B*58:01 for allopurinol, and HLA-B*57:01 for abacavir. This article aims to update the current knowledge in the field of pharmacogenomics of drug hypersensitivities or SCAR, and its implementation in the clinical practice.